PROGRAM “LOMBOK RAWIT” SEBAGAI SARANA TERAPI BAGI ANAK TUNALARAS - Exwan A.V; Akhmad Rivai; Riska Putri; Niwang Tungung (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
Student Creativity Program of "Lombok Rawit" standing for Latihan AmongBekso dan Karawitan (practicing dancing and playing gamelan) is motivated by a willto make the traditional Javanese gamelan music and dance as a means of therapy formentally retarded students. Through this program, the mentally retarded children areexpected to be familiar with the Javanese culture, while getting a therapy to reduceemotional and behavioral deviations. This program is implemented to the mentallyretarded children in Special School E Prayuwana Yogyakarta. There are 25 students inthe school. The training was conducted from April to July, 2014. The results achievedafter the training are (1) the increase of the value of the post-test is by 68%. This percentageis obtained from the tabulated results from the instrument, which show areduction in the number of occurrences. The characteristics of mentally retardedchildren are hyperactivity, fear, antisocial, etc. (2) The team of this program manage tohold a simple form of collaborative performances of gamelan and dance by thechildren. (3) The team also manage to compile teaching materials in the form of modulesand CD of gamelan and dance lessons for children so that it can be used widelyby teachers and therapists of mentally retarded children. Based on the results of theprogram, it can be concluded that the training of "Rawit Lombok" can be used as atherapeutic tool for such children. Based on the effectiveness of this program, theteam of the program try to do a follow up in the form of mentoring and socialization,so that a similar program can be applied to other mentally retarded children in otherschools.